Pengaruh Senam Lansia Terhadap Tekanan Darah Pada Usia Pertengahan Dengan Hipertensi di UPTD Puskesmas Cibeber Kecamatan Cibeber Kabupaten Cianjur Tahun 2023 - Marisca Agustina; Lina Herlinawati; Ahmad Rizal (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
Introduction: High blood pressure (hypertension) is an increase in blood pressure in the arteries. Health problems in elderly people are often related to decreased organ function which causes degenerative diseases, including hypertension. This condition needs to be watched out for because it often does not show any special symptoms, so many people are not aware of it and still feel healthy to carry out daily activities. Therefore, hypertension is often referred to as a silent killer.Method: The research method applied in this study is a quantitative approach using a pre-experimental design with a one-group pre-post test design model.Research Results: The average blood pressure before doing elderly exercise (pretest) was 151.94/93.66 mmHg, while after doing elderly exercise (post-test) it was 137.90/87 mmHg. There is a significant effect of elderly exercise on blood pressure in middle-aged hypertensive patients at UPTD Cibeber Health Center.Conclusion: Based on the results obtained, it can be concluded that providing elderly exercise has a significant influence on the blood pressure of middle-aged hypertensive patients at the Cibeber Health Center UPTD